The Role of Teachers in Facing Radicalism Threats at Al-Kautsar Labschool Middle School, Bandung - Risa Rizania; Fauzia Gustarina Cempaka Timur; Rudy Sutanto (CV. AFDIFAL MAJU BERKAH, 2023)
Indonesia, with the world's largest Muslim population, faces serious challenges related to radicalism and terrorism. The threat of radicalism in Indonesia has spread to various aspects of life, including educational institutions, both formal and informal. This study aims to analyze the role of teachers in addressing the threat of radicalism at Al-Kautsar LabSchool Middle School in Bandung. The main theories used in this research are the theories of radicalism and the concept of the teacher's role. This research employs a qualitative approach, where data is collected through interviews and literature review. The results of this study reveal nine roles of teachers at Al-Kautsar LabSchool Middle School (SMP Al Kautsar LabsSchool) in facing the threat of radicalism, including being informants, organizers, motivators, directors, initiators, transmitters, facilitators, mediators, and negotiators. This research provides a detailed explanation of these nine roles based on the elaboration of concepts from the Ministry of Religious Affairs and Sadirman AM in addressing the threat of radicalism at SMP Al Kautsar LabsSchool. Additionally, the researcher also analyzes the concept of the teacher's role in the policy options from the Ministry of Education and Culture (Kemendikbud) research in 2018 and the strategic plan of the National Counterterrorism Agency (BNPT) for 2020-2024 to combat radicalism in the school environment.